Analisis Kinerja Inspektorat Daerah Dalam Melakukan Fungsi Pengawasan (Studi Pada Inspektorat Kota Langsa) - Novita, Dilla; Kadir, Abdul; Siregar, Nina Siti Salmaniah (Universitas Medan Area, 2020)
The main task of the Langsa City Inspectorate is to carry out oversight of the implementation of Government affairs in the region, and the implementation of guidance on the implementation of Regional Government. But in reality there are still problems that occur at the Langsa City Inspectorate. Based on the background of the problem, the formulation of the problem in the study is Â What is the performance of the Inspectorate in carrying out the supervisory function at the Inspectorate in carrying out the supervisory function. Factors that influence the performance of the Inspectorate in carrying out the supervisory function.The research objective is to analyze Â the performance of the Inspectorate in carrying out the supervisory function. Factors that influence the performance of the Inspectorate in carrying out the supervisory function. The research method used was descriptive with qualitative analysis. Data collection was obtained from interviews, documentation and observation. The results of the study are The performance of the regional inspectorate in carrying out the supervisory function in Langsa City in terms of productivity, service orientation, responsiveness and accountability in general has not been effective, apparently not yet effective. While the suggestions from the research are Â Regulations or laws are needed which regulate internal supervision. There is a need for commitment and hard work and the seriousness of the supervisory apparatus in the Inspectorate in carrying out the supervisory function. As an institution that has a strategic role as supervisor of Government in the region, it is very important to increase effectiveness. Increasing the work ethic of examiners is a determining factor for the success of the organizational mechanism.